Acquisition of Nouns Derived from a Verb of English as L2 - Vargas Vega, Brenda; Velásquez Upegui, Eva Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
There are several studies on the morphological acquisition of English as L2 but the errors committed by the participants have not been studied in depth. The objective in this article is to analyze the errors in a derivation test to determine percentage and typo - logical differences between Mexican participants with different proficiency in English. The methodology was exploratory of quasi-experimental type. It focused on four nominalizing suffixes controlling their level of difficulty and productivity, and the cognate status and frequency of nouns. The design of the test was based on the proposal of Carlisle (2000). The errors were classified following Marín (2013) and analyzed based on the levels of difficulty in acquiring English affixes from Bauer and Nation (1993) and the morpholog- ical derivation knowledge aspects of Tyler and Nagy (1989). The results show that both the percentage and the type of errors vary according to the level of proficiency of the participants. A large percentage of use of inflectional suffixes was found, that is, of lower difficulty level; and it was evidenced that the distributional knowledge of the suffixes is the last to be acquired. These findings may be useful for teaching purposes